Capitalist flattening or flattening capitalism? class forces and political choices in the global knowledge economy. (1st July 2007) - ,
Abstract : The global knowledge economy is new, but its central drivers are not. Capitalist logics continue to set its trajectory. The character and strength of class forces continue to determine its development and outcomes. As industrial conditions standardise globally and as trade flows thicken, the class compacts established in core capitalisms in the immediate post-war period are everywhere under challenge, and the task for the Left is clear: to create and integrate movements capable of replacing that reactionary and capitalist logic with a progressive and socialist one.